Potential Benefit of Add-on Δ9-Tetrahydrocannabinol in Pediatric Drug-Resistant Epilepsy: A Case Series. (29th July 2022) - Nowicki, Magda; Bourgeois-Tardif, Sandrine; Diaz, Patrick L.; Hebert, Francois Olivier; Sanon, Nathalie T.; Champagne, Pierre-Olivier; Major, Philippe; Sell, Erick; Bitton, Jonathan; Lewis, Evan; Weil, Alexander G.
ABSTRACT: We present five cases of pediatric drug-resistant epilepsy (DRE) that failed management using high cannabidiol (CBD) doses, but had significant reduction in seizure frequency with reintroduction or increasing doses of tetrahydrocannabinol (THC). There is growing evidence supporting the use of whole-plant CBD-rich extracts (containing THC and other cannabinoids) in the treatment of pediatric DRE. Based on our experiences and reports in the literature, we propose that, in patients who fail management with an initial trial of high-dose CBD-focused therapy, there may be a role for add-on THC-focused formulations.